2D image to 3D CAD model mapping of a T-joint pipe mapping for an intuitive robot teaching system - Liu, Ying. (2013)
This report presents the mapping process for 2D image with 3D CAD model of cylinders and T-joint pipes. The mapping is the critical process to conduct the intuitive robot path teaching to complete the welding tasks. This project aims to improve the intuitive method for robot path teaching using augmented reality technology. The system setup and augmented reality environment was developed by SimTech.